2007
DOI: 10.1007/s12103-007-9003-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Higher Education Decisions of Criminal Justice Professionals

Abstract: Criminal justice professionals are a potential source of students for many criminal justice programs, especially those in metropolitan areas. This study explored factors that influenced the higher education decisions of 480 Northwestern Ohio criminal justice employees (e.g., municipal police officers, sheriff deputies, jail staff, and prison staff). Most indicated a desire to pursue higher education. Among those indicating an interest in earning a degree, cost and convenience were the most significant factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…It is within this context that justice agencies attempt to balance heightened standards for new hires with requirements that are too stringent and eliminate a sizeable portion of the potential applicant pool. Institutions of higher education can facilitate agency recruitment initiatives by offering degree programs tailored to those seeking positions in the justice professions, degree completion options for in-service personnel who need flexible options to balance their professional and personal responsibilities while studying (Hall, Ventura, & Lambert, 2007), and opportunities for potential applicants to entry-level justice system positions who are as yet undecided on a career path. All three of these groups can be incentivized by academic credits being awarded for their professional, or even personal, experiences.…”
Section: Higher Education For Justice System Personnelmentioning
confidence: 99%
“…It is within this context that justice agencies attempt to balance heightened standards for new hires with requirements that are too stringent and eliminate a sizeable portion of the potential applicant pool. Institutions of higher education can facilitate agency recruitment initiatives by offering degree programs tailored to those seeking positions in the justice professions, degree completion options for in-service personnel who need flexible options to balance their professional and personal responsibilities while studying (Hall, Ventura, & Lambert, 2007), and opportunities for potential applicants to entry-level justice system positions who are as yet undecided on a career path. All three of these groups can be incentivized by academic credits being awarded for their professional, or even personal, experiences.…”
Section: Higher Education For Justice System Personnelmentioning
confidence: 99%
“…Higher education has been presumed to make police more efficient at performing their jobs, as Hall, Ventura and Lambert (2007), Finckenhauer (2005) among many others profess that higher education is essential to police professionalism, and that a four-year degree improves performance (Aamodt, 2004;Breci, 1997;Cascio, 1977;Cunningham, 2006;Kappeler, Sapp, & Carter, 1992;Scott, 1986;Sherman, 1978;Shernock, 1992;Smith & Aamodt, 1998;Varricchio, 1998;Worden, 1990). Furthermore, Carlan and Byxbe (2000) illustrated "higher education seems to deliver a more humanistic candidate for police work" (p. 243).…”
Section: Research Problemmentioning
confidence: 99%
“…Mayo (2006) estimated between 25 and 30% of police officers possess a fouryear degree, which realistically mirrors the 29.9% of the US adult working population over the age of 25 currently holding a baccalaureate degree (United States Bureau of the Census, 2010). Hall et al (2007) found among 480 criminal justice employees surveyed were highly interested in obtaining a college degree; therefore, the desire to pursue higher education is evident among municipal police officers, sheriff's deputies, and other criminal justice personnel.…”
Section: Status Of College Degrees Among Police Officersmentioning
confidence: 99%